L’hôtel de région de Midi-Pyrénées - Roland Chabbert (In Situ)
The ‘hôtel de région’ at Toulouse, an administrative centre for the newly created Midi-Pyrénées region, is one of the first of such buildings to be established in France in the mid-1980s. It was decided to create a new building which would affirm the meaning and modernity of the institution. Jean-Pierre Estrampes, an architect trained in the United States, was commissioned to design a functional building. If the references to American architecture are obvious, the deliberate use of local building materials suggests that the politicians and the architect also wanted to anchor the building in its regional context. Two recent extensions (2009 and 2011) today complete this building designed for regional institutions by Estrampes. These extensions are the works of Jérôme de Boisseson, Jean-Michel Dumas and Philippe-Victoire de Vilmorin for the first, and Jacques Munvez and Pierre-Luc Morel for the second. Together, they accommodate staff in charge of the new missions of the regional administration. Built more than thirty years ago, certain parts of the centre have witnessed new uses but the premises originally designed by Jean-Pierre Estrampes have only seen marginal structural alterations. For some years now, work has been carried out to bring the building up to contemporary safety and service requirements.